Islamic Legal Policy on Ultra-Micro Enterprise Financing and Its Implementation from the Perspective of Maqāṣid al-Sharī‘a - Diatmoko, Tri; Absori, Absori; Wardiono, Kelik; Nashirudin, Muh; Budiono, Arief (Al-Ahkam, 2025)
Until the mid-19th century, the Dutch colonialism (the Western world) began to intervene in the indigenous legal systems of Indonesia. The current situation marks the beginning of a decline in the civilization of Muslims, particularly in Indonesia. This development raises concerns about the future of Indonesian society as a whole. This decline permeated various aspects of life, including the field of mu’āmala law, which began to adopt usury-based concepts. This research aims to reconstruct the Islamic legal policy on Ultra-Micro (UMi) Financing as practiced by the Indonesian government, which still contains elements of usury (ribā) in its implementation. This study employs a qualitative approach using empirical-socio-legal research methods involving an analysis of UMi Financing contracts, interviews with stakeholders, and direct observations in Surakarta. The analysis is grounded in the theory of maqāṣid al-sharī’a, including the principles of ribā as outlined in classical Islamic jurisprudence (turāth). The findings reveal a research gap that the current legal policy on Sharia ultra-micro financing implemented by the government had ribā, which is found in classical Islamic texts.